Democratic Republic of Sao Tome and Principe : Third Review Under the Extended Credit Facility Arrangement and Financing Assurances Review-Press Release; Staff Report; and Statement by the Executive Director. (IMF Staff Country Reports; Country Report ;, 2021)
Sao Tome and Principe has maintained macroeconomic stability in the period since the previous ECF review (February 2021). International support and the authorities' swift actions helped mitigate the impact of the pandemic so far. Growth is estimated at 3 percent in 2020, supported by externally-financed spending. Growth is projected to slow to 2 percent in 2021, reflecting delays in the return of tourists, and to strengthen to 3 percent in 2022. The economic outlook is subject to high uncertainty and downside risks, notably the evolution of the pandemic.